2011
DOI: 10.1021/ja2073033
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Avidity on Linker Length for a Bivalent Ligand–Bivalent Receptor Model System

Abstract: This paper describes a synthetic dimer of carbonic anhydrase, and a series of bivalent sulfonamide ligands with different lengths (25 to 69 Å between the ends of the fully extended ligands), as a model system to use in examining the binding of bivalent antibodies to antigens. Assays based on analytical ultracentrifugation and fluorescence binding indicate that this system forms cyclic, noncovalent complexes with a stoichiometry of one bivalent ligand to one dimer. This dimer binds the series of bivalent ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 36 publications
(86 reference statements)
3
101
0
Order By: Relevance
“…Several examples of engineering polyvalent biological interactions have been described (68), and specific examples where polyvalency increases the potency of fusion inhibitors (69,70) or entry inhibitors (17) have been reported. For HRC fusion inhibitors, dimerization/multimerization (45,53) reduces the k off of the inhibitor-fusion protein complex formation in an effect that has been termed the "avidity effect" (71). The lipophilic tag, on the other hand, increases the k on for complex formation (45) by targeting the peptide to the cell membrane where the virus fuses, increasing the local peptide concentration.…”
Section: Figmentioning
confidence: 99%
“…Several examples of engineering polyvalent biological interactions have been described (68), and specific examples where polyvalency increases the potency of fusion inhibitors (69,70) or entry inhibitors (17) have been reported. For HRC fusion inhibitors, dimerization/multimerization (45,53) reduces the k off of the inhibitor-fusion protein complex formation in an effect that has been termed the "avidity effect" (71). The lipophilic tag, on the other hand, increases the k on for complex formation (45) by targeting the peptide to the cell membrane where the virus fuses, increasing the local peptide concentration.…”
Section: Figmentioning
confidence: 99%
“…In the context of intracellular transport where kinesin-1 functions as a tetramer containing two KLCs held together by a coiled-coil region and both SKIP motifs contribute to transport (7,13), it is tempting to speculate that both chains can contribute to the binding of the W-acidic cargo pair. For SKIP, the higher affinity WD motif would direct the first binding event to one of the KLC TPR with avidity effect promoting the association of the WE motif to the other KLC (20,21). It will be important to determine this relationship to the kinesin-1 tetramer and examine the importance of cargo induced TPR conformational change in motor activation.…”
mentioning
confidence: 99%
“…[13][14] In the case of carbonic anhydrase, only studies on bivalent inhibitors were recently reported.I ndeed, Whiteside'sr esearch group describedi n2 012 the binding of monovalent and bivalent benzene sulfonamide ligandst oasynthetic dimer of carbonic anhydrase. [15] The group of Neri reported the use of bivalent small molecule ligand-drug conjugates against carbonic anhydrase IX. [16] Besides the classical small-molecule approach, which has been applied with some successo nt he in vitro and in vivo inhibition of human CA (hCA), the use of multivalent nanoplatforms could therefore be of great interesta nd a promising strategy in this field.…”
mentioning
confidence: 99%